Struktura nadezhnosti zashchitnykh taktiko-tekhnicheskikh deistvii dzyudoistov vysokoi kvalifikatsii - Eganov, A. V.; Miller, A. E. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The aim of this study was to investigate the structure of defensive tactical and technical actions in competition of high-level judo-wrestlers.